2018
DOI: 10.1038/s41396-017-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Deposition rates of viruses and bacteria above the atmospheric boundary layer

Abstract: Aerosolization of soil-dust and organic aggregates in sea spray facilitates the long-range transport of bacteria, and likely viruses across the free atmosphere. Although long-distance transport occurs, there are many uncertainties associated with their deposition rates. Here, we demonstrate that even in pristine environments, above the atmospheric boundary layer, the downward flux of viruses ranged from 0.26 × 10 to >7 × 10 m per day. These deposition rates were 9-461 times greater than the rates for bacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
185
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(195 citation statements)
references
References 49 publications
10
185
0
Order By: Relevance
“…dry or wet; Triadó‐Margarit, Calíz, Reche, & Casamayor, ). Reche, D'Orta, Mladenov, Winget, and Suttle () observed that the rates of bacterial deposition at two locations at the peak of Sierra Nevada in South‐eastern Spain were higher during rain with the intrusion of dust from the Sahara Desert (i.e. air masses from northern Africa) than during only dry deposition event.…”
Section: Discussionmentioning
confidence: 99%
“…dry or wet; Triadó‐Margarit, Calíz, Reche, & Casamayor, ). Reche, D'Orta, Mladenov, Winget, and Suttle () observed that the rates of bacterial deposition at two locations at the peak of Sierra Nevada in South‐eastern Spain were higher during rain with the intrusion of dust from the Sahara Desert (i.e. air masses from northern Africa) than during only dry deposition event.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, a number of studies have shown that airborne transmission route could spread viruses even further the close contact with infected people [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Paules et al (2020) highlighted that -besides close distance contacts -airborne transmission of SARS-CoV can also occur [5].…”
Section: Introductionmentioning
confidence: 99%
“…Closely related viruses occurring in blooms on opposite sides of the globe, while remarkable, is consistent with reports from both marine and freshwater systems (Short and Suttle, ; Sabehi et al ., ; Holmfeldt et al ., ). A recent study demonstrated that viruses are dispersed across distant ecosystems via atmospheric transport and deposition of dust and aerosolized particles of marine origin, providing a compelling explanation for this commonly observed phenomenon (Reche et al ., ).…”
Section: Resultsmentioning
confidence: 97%